PENINGKATAN KAPASITAS SUMBER DAYA MANUSIA GUNA MENINGKATKAN DAYA SAING USAHA - Nolla Puspita Dewi; Benni Sumarman; Nurhatisyah; Widyanti Diah Lestari; Nicha Suwalla (LPPM-Universitas Batam, 2024)
In today's fast-changing and competitive business era, the application of an effective human resource management approach is essential to sustain business progress. Furthermore, this dedication report explores the various ways in which organizations can achieve sustainable progress by implementing human resource management strategies that emphasize innovation, sustainability, and ethics. The method of implementing community service uses a qualitative approach with the type of Participatory Action Research (PAR). Participatory Action Research is a relevant method related to community empowerment with the application of three steps, including planning, action, and evaluation. Furthermore, community service activities that focus on increasing the capacity of human resources to increase competitiveness as business capital run in a systematic way.